2020
DOI: 10.1021/acs.jced.9b00948
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Light Alkanes and Alkenes on Activated Carbon and Zeolite 13X at Low Temperatures

Abstract: The separation of short-chained alkanes and alkenes is challenging because of their chemical similarity and thus being costly in energy. The implementation of a cryogenic adsorption process may overcome this problem, but systematic studies on light hydrocarbon adsorption at low temperatures are virtually lacking. Therefore, as a first step, in this paper, we present single-component adsorption isotherms of ethane, ethylene, propane, and propylene on activated carbon (AC) and zeolite 13X for temperatures of −80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…and Li + exchanged 13X(Grande et al, 2010) demonstrated successful separation of ethylene and propylene from their paraffin counterparts. The p-complexation has also been exploited by different types of lattice cations of zeolite-based materials, like, zeolite 13X(Schmittmann et al, 2020;Pu et al, 2018),ITQ-32 (Gutie ´rrez-Sevillano et al, 2010;Palomino et al, 2007) carbon-nanotube doped-ZSM-58(Selzer et al, 2018) and aluminosilicates(Luna-Triguero et al, 2020). A systematic study was performed to understand the role of few metals in influencing pi complexation in zeolite materials.…”
mentioning
confidence: 99%
“…and Li + exchanged 13X(Grande et al, 2010) demonstrated successful separation of ethylene and propylene from their paraffin counterparts. The p-complexation has also been exploited by different types of lattice cations of zeolite-based materials, like, zeolite 13X(Schmittmann et al, 2020;Pu et al, 2018),ITQ-32 (Gutie ´rrez-Sevillano et al, 2010;Palomino et al, 2007) carbon-nanotube doped-ZSM-58(Selzer et al, 2018) and aluminosilicates(Luna-Triguero et al, 2020). A systematic study was performed to understand the role of few metals in influencing pi complexation in zeolite materials.…”
mentioning
confidence: 99%
“…Due to the higher molecular weight and larger polarizability, ethane was reported to have higher selectivity over ethylene on the AC surface, and the π−πinteractions between ethylene molecules and the polar molecules on the surface did not influence the adsorption performance considerably. 60 Both ethane and ethylene form C−H−N/O bonds with electronegative atoms like nitrogen and oxygen present on the AC, but ethane forms stronger bonds, as sp 3 hybridized carbons interact homogeneously with oxygen and nitrogen, whereas, in the case of olefin, sp 2 hybridized carbons interact with the surface at a certain angle resulting in weaker interactions. 113 Graphitized carbon black with slit pores lined with graphene layers was also investigated for its potential in ethane/ethylene separation, and molecular simulation results stated that at low gas loadings, solid−fluid interactions are significant whereas, at high loadings, fluid−fluid interactions become the deciding factor in the adsorption process.…”
Section: Reverse Selectivitymentioning
confidence: 99%
“…Ethane is more polarizable than ethylene and thus a temporary dipole moment can be induced in ethane. As ethane molecules have higher evaporation enthalpy than the ethylene ones, ethane molecules interact with each other more than the ethylene molecules do, resulting in stronger lateral interactions with the adsorbate surface . This specific binding of ethane molecules can be reversed by fine-tuning the surface via functionalization.…”
Section: Selectivity Tuning Of Adsorbentsfunctionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In their production process, water has to be removed from complex reacting mixtures containing formaldehyde, methanol, methylal, and OME [1]. Besides membranes, adsorption has been proposed for the task of water removal from these mixtures [2]. However, no reliable equilibrium data for the adsorption of water and the potential co-adsorption of other species is available, neither for the above-mentioned mixtures nor for the very common industrially relevant mixtures of water, methanol, and formaldehyde.…”
mentioning
confidence: 99%